How to Avoid Common Problems with Leaf Wetness Sensor Installation and Maintenance - Thiago Borba Onofre; Clyde W. Fraisse; Natalia A. Peres; Janise McNair (EDIS)
Leaf wetness duration is an essential input in disease prediction models and decision support systems in Florida and elsewhere. Incorrect installation or lack of regular maintenance of leaf wetness sensors may lead to errors in plant disease risk monitoring and negative impacts on yield. This 7-page publication provides detailed guidelines for the proper installation and maintenance of leaf wetness sensors and describes the most common problems found in field installations as well as potential solutions. Written by T. B. Onofre, C. W. Fraisse, N. A. Peres, and J. McNair, and published by the UF/IFAS Department of Agricultural and Biological Engineering, February 2020.